2014
DOI: 10.1080/17450128.2014.925170
|View full text |Cite
|
Sign up to set email alerts
|

Accessing general and sexual healthcare: experiences of urban youth

Abstract: Urban adolescents face many barriers to health care that contribute to health disparities in rates of sexually transmitted infections (STIs) and unintended pregnancy. Designing interventions to increase access to health care is a complex process that requires understanding the perspectives of adolescents. We conducted six focus groups to explore the attitudes and beliefs about general and sexual health care access as well as barriers to care among urban, economically disadvantaged adolescents. Participants fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Guided by the TPB in the focus group and survey methods, the data were targeted to address the perceptions of adolescent driver inattention of attitudes, PBCs, and norms that could then influence intentions and eventually behavior. The focus group findings helped to contextualize quantitative survey results, as well as provide realistic scenarios and strategies for the intervention participants (Miller, Wickliffe, Jahnke, Linebarger, & Dowd, 2014). For example, adolescents in the study overwhelmingly reported unfavorable attitudes towards texting while driving.…”
Section: Discussionmentioning
confidence: 99%
“…Guided by the TPB in the focus group and survey methods, the data were targeted to address the perceptions of adolescent driver inattention of attitudes, PBCs, and norms that could then influence intentions and eventually behavior. The focus group findings helped to contextualize quantitative survey results, as well as provide realistic scenarios and strategies for the intervention participants (Miller, Wickliffe, Jahnke, Linebarger, & Dowd, 2014). For example, adolescents in the study overwhelmingly reported unfavorable attitudes towards texting while driving.…”
Section: Discussionmentioning
confidence: 99%
“…Conversations about HPV focused on recommendations and discussing efficacy of vaccines (Gilkey et al, 2015; Lee, 2017; Mullins et al, 2013). The remaining five articles did not specify types of STIs; one article described STI testing (Helitzer et al, 2011), but details of conversations were unavailable for the other four articles (Miller et al, 2014; O'Sullivan et al, 2010; Seburg et al, 2015; Snyder et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Adequate adherence levels can reduce HIV acquisition among MSM by >90% [5,6,41,43], and increasing the effective use of PrEP among YMSM—one of the highest-risk groups for new infections—is one of the leading priorities for HIV prevention. However, YMSM face multiple challenges in initiating and adhering to PrEP [44], and, in 2 open-label studies of PrEP use by YMSM aged 15-17 and 18-22 years (ATN 113 and 110) [8,9], adherence was suboptimal after 3 monthly visits, and the HIV incidence was high (6% and 3%, respectively).…”
Section: Discussionmentioning
confidence: 99%